Pricing ArcelorMitall steel globally : the effects of currency changes - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
International companies can often face marketing challenges as a result of the intricacies of international finance. This case study focuses on ArcelorMittal, the world's largest steel manufacturer, and the pricing challenges that the company faces due to ever changing exchange rates and fluctuating costs.